DIRECTIONAL MOTION VERB CONSTRUCTION IN MADURESE LANGUAGE: A STUDY OF LANGUAGE TYPOLOGY - Sahila Rizqy, Muhammad Hifni; Subiyanto, Agus (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2023)
Semantically, the construction of directional motion verbs has two significant points: manner of motion, which refers to the way the motion is performed, and path, which conveys the directional meaning. In the context of verbal construction with directional motion, the path component can be constructed through directional verbs or prepositional phrases as markers of the goal. Based on these patterns, Talmy (1975) and Slobin (2006) classified languages into three frameworks: verb-framed languages, satellite-framed languages, and equipollent-framed languages. This research aims to describe the construction of direct motion verb in Madurese language and critically analyze the position of Madurese as an Austronesian language based on the classification proposed by Talmy and Slobin. Using a descriptive-qualitative approach, this study collects primary data from native Madurese speakers, and the secondary data from article journal related to Madurese language as comparison. In conclusion, Madurese language can be categorized as a verb-framed language overall. Based on the analysis, there are several directional verbs in Madurese that can simultaneously carry meanings consistent with prepositional phrases, although in other sentence contexts, they may exhibit different semantic and syntactic patterns. Furthermore, Madurese tends to fall into the verb-framed language category as it lacks a resultative-adjective pattern, and its directional verbs are not main verbs but rather open-class adjuncts.